Impact of shift work on women's reproductive function - a review of the literature - Justyna Sak; Michał Nowiński; Laura Fus-Mazurkiewicz; Dominika Król; Wojciech Mazurkiewicz (Termedia Publishing House, 2024)
Infertility is becoming more of a growing health problem every year. It affects women at a slightly higher rate than men of childbearing age. Shift work, including night work, is undertaken by a relatively large proportion of the population. Sleep is essential for the proper functioning of the human body. There is a growing body of scientific evidence supporting the fact that both partial sleep deficiency and total sleep deprivation are associated with reproductive dysfunction in women. This can cause difficulties in conceiving a child. It seems that an attempt to eliminate this problem could be made by hiring more workers, which would translate into less strain on individual workers. The purpose of this study was to present the current state of knowledge on the impact of shift work on women's reproductive functions. To this end, internet databases were reviewed, using the words: female infertility, sex steroid hormones, circadian rhythm, night shift work.